2006
DOI: 10.1152/japplphysiol.00515.2006
|View full text |Cite
|
Sign up to set email alerts
|

Motor training induces experience-specific patterns of plasticity across motor cortex and spinal cord

Abstract: The motor cortex and spinal cord possess the remarkable ability to alter structure and function in response to differential motor training. Here we review the evidence that the corticospinal system is not only plastic but that the nature and locus of this plasticity is dictated by the specifics of the motor experience. Skill training induces synaptogenesis, synaptic potentiation, and reorganization of movement representations within motor cortex. Endurance training induces angiogenesis in motor cortex, but it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
356
2
43

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(427 citation statements)
references
References 81 publications
12
356
2
43
Order By: Relevance
“…Firstly, the activation of previously latent neural networks in residual tissue may take on the function of the lost tissue (Sigler et al, 2009); alternatively, enhanced axonal sprouting, synaptogenesis, and dendritic spine turnover (Biernaskie and Corbett, 2001;Brown et al, 2007Gonzalez and Kolb, 2003;Stroemer et al, 1995;Winship and Murphy, 2009) may support reorganization of residual tissue such that it can support the function of the lost tissue. Again, the application of plasticity promoting factors such as environmental enrichment (Williams et al, 2006), behavioural therapy (Adkins et al, 2006;Kleim et al, 2004), pharmacological treatments (MacDonald et al, 2007), and neurotrophic factor application (Monfils et al, 2005) have been shown to facilitate reorganization of cortical maps.…”
Section: Electrophysiological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the activation of previously latent neural networks in residual tissue may take on the function of the lost tissue (Sigler et al, 2009); alternatively, enhanced axonal sprouting, synaptogenesis, and dendritic spine turnover (Biernaskie and Corbett, 2001;Brown et al, 2007Gonzalez and Kolb, 2003;Stroemer et al, 1995;Winship and Murphy, 2009) may support reorganization of residual tissue such that it can support the function of the lost tissue. Again, the application of plasticity promoting factors such as environmental enrichment (Williams et al, 2006), behavioural therapy (Adkins et al, 2006;Kleim et al, 2004), pharmacological treatments (MacDonald et al, 2007), and neurotrophic factor application (Monfils et al, 2005) have been shown to facilitate reorganization of cortical maps.…”
Section: Electrophysiological Changesmentioning
confidence: 99%
“…The size and organization of the "motor map" is altered in response to, and is thus indicative of, cortical injury (Gharbawie et al, 2005;Nudo, 1997;Williams et al, 2006), corticofugal fiber function (Kartje-Tillotson et al, 1987), and motor experience/learning (Adkins et al, 2006;Jacobs and Donoghue, 1991;Kleim et al, 1998Kleim et al, , 2002. Changes in ICMS motor map organization are also often used as a measure of peri-infarct tissue function after focal cortical stroke (Gharbawie et al, 2005).…”
Section: Electrophysiological Implications Of the Plastic Modelmentioning
confidence: 99%
“…The latter effects of exercise on cells in the hippocampus may be due, in part, to imposition of a mild stress on the nerve cell during exercise, because levels of several molecular markers of mild stress are increased in response to exercise, including BDNF and vascular endothelial cell growth factor (Cotman et al, 2007). Of course, motor neurons and neurons in the motor cortex, striatum, and cerebellum that effect and control exercise are themselves highly active (and therefore energetically, ionically, and oxidatively stressed) during exercise (Adkins et al, 2006). Neurons in many regions of the brain are "exercised" during cognitive processing of information and are therefore subjected to the same kinds of stress that motor neurons experience during physical exercise.…”
Section: Physical and Mental Exercise And Neurohormesismentioning
confidence: 99%
“…The adult brain shows a remarkable capacity for morphological alterations during learning or adaption to a changing environment (Markham and Greenough, 2004;Adkins et al, 2006;Draganski and May, 2008). In human subjects, gray and white matter changes can be observed after intensive long-term motor skill learning for several months (Draganski et al, 2004;Scholz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%